2021
DOI: 10.35848/1347-4065/abe05e
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of PDMS-based volume Bragg gratings by stitching of femtosecond laser filament

Abstract: This work demonstrates the fabrication of poly-(dimethylsiloxane) (PDMS)-based volume Bragg gratings (VBGs) by stitching of femtosecond laser filament. The refractive index change induced by femtosecond laser pulses is low (orders of 10−4 to 10−3) in PDMS. Therefore, the VBG thickness is the key parameter to fabricate high-efficiency VBGs in PDMS. With the intention of increasing diffraction efficiency, this paper presents fabrication of multi-layered PDMS-based VBGs. We produce VBGs with 10 μm line pitch usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Methods based on lithography (E-beam, multibeam interference, nanoimprinting, and digital projection) have been widely used to fabricate nano-/microstructures on hydrogel surfaces and modify their refractive indices (RI) and light shaping properties . However, for subsurface or volumetric processing of hydrogels in a user-defined manner, two-photon-absorption-based laser writing may be the only realistic method of choice as it can generate customized patterns within ordinary hydrogels with high design flexibility in 3D. Being embedded within a hydrogel matrix, printed structures are free from optical misalignment issues or damage during handling yet facilitate the modulation of pattern periodicity via analyte diffusion within the porous matrix. Previously, our group showed that femtosecond (fs) laser writing can generate “densified” structures within ordinary gelatin-based hydrogels, which can be used as biophysical cues to align cells encapsulated within the gelatin matrix .…”
Section: Introductionmentioning
confidence: 99%
“…Methods based on lithography (E-beam, multibeam interference, nanoimprinting, and digital projection) have been widely used to fabricate nano-/microstructures on hydrogel surfaces and modify their refractive indices (RI) and light shaping properties . However, for subsurface or volumetric processing of hydrogels in a user-defined manner, two-photon-absorption-based laser writing may be the only realistic method of choice as it can generate customized patterns within ordinary hydrogels with high design flexibility in 3D. Being embedded within a hydrogel matrix, printed structures are free from optical misalignment issues or damage during handling yet facilitate the modulation of pattern periodicity via analyte diffusion within the porous matrix. Previously, our group showed that femtosecond (fs) laser writing can generate “densified” structures within ordinary gelatin-based hydrogels, which can be used as biophysical cues to align cells encapsulated within the gelatin matrix .…”
Section: Introductionmentioning
confidence: 99%
“…A rapid prototyping technique for 3D PDMS microfluidic devices with a low surface roughness of 0.361 nm was demonstrated utilizing a red femtosecond laser to produce a metallic mold, which was then directly used for the replica molding of PDMS [25]. PDMS-based volume Bragg gratings (VBGs) were successfully fabricated by stitching of the femtosecond laser filament, and the diffraction efficiency has been experimentally investigated by varying the scanning speed, energy, number of layers, and spacing between layers [26]. Experimental investigations showed that direct writing of copper (Cu) patterns on PDMS using femtosecond laser could induce thermochemical reduction of the glyoxylic acid copper (GACu) complex [27].…”
Section: Introductionmentioning
confidence: 99%